2021
DOI: 10.1007/s10864-021-09460-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Intervention Session Length Matter? A Comparison of a Math Intervention Across Three Durations

Abstract: Understanding how to intensify an intervention is critical to implementing responseto-intervention (RtI), a tiered, problem-solving framework to deliver evidence-based interventions per student needs. Research and practice guidelines provide conflicting recommendations for delivering math interventions (i.e., treatment intensity) within RtI. The present study used an adapted alternating treatment design to examine the impact of varying the session length, or number of minutes per intervention session, on stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Intervention length did moderate the effect on math anxiety, longer interventions had a larger effect on math anxiety than shorter ones, although Short, Medium, and Long interventions were all effective. Previous research has suggested that longer interventions are more desirable in the context of enhancing math performance, although shorter interventions can be just as efficient (DeFouw et al, 2021). The results from our meta-analysis are in line with the assumption that longer interventions are more efficient, possibly due to the duration and the number of sessions that a longer intervention can entail.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Intervention length did moderate the effect on math anxiety, longer interventions had a larger effect on math anxiety than shorter ones, although Short, Medium, and Long interventions were all effective. Previous research has suggested that longer interventions are more desirable in the context of enhancing math performance, although shorter interventions can be just as efficient (DeFouw et al, 2021). The results from our meta-analysis are in line with the assumption that longer interventions are more efficient, possibly due to the duration and the number of sessions that a longer intervention can entail.…”
Section: Discussionsupporting
confidence: 88%
“…In math performance research, interventions that vary in the number of sessions and length have been conducted, yet it is still unclear if there is a preferred design to utilize when executing an intervention, as shorter interventions with fewer sessions can be equally efficient as longer ones (DeFouw et al, 2021). For example, Schnepel and Aunio (2022) concluded in their review that the most efficient interventions were those that consisted of at least two sessions per week, while other researchers endorse interventions that are intensified in terms of session length and duration, and that are offered up to four times per week to increase the likelihood of progress (DeFouw et al, 2021). However, in the domain of math anxiety interventions, no previous studies have investigated the effect of intervention length in reducing math anxiety.…”
mentioning
confidence: 99%
“…Despite this, we think it may be important to replicate findings of this study with measures of need satisfaction or autonomous motivation that exhibit acceptable levels of reliability. Finally, though exposures of five weeks and shorter showed its efficiency (McNaughton-Cassill et al 2000;Fjeldsoe et al 2011;DeFouw et al 2021;Kiyono et al 2022) a longer exposure could have produced a stronger effect (Bolier et al 2013), which can be further examined in future research.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to examining the overall effect of GEAR UP on educational outcomes, we aimed to investigate whether the length of participation moderated the overall effect. Research has shown that the length of intervention can play a pivotal role in learning (DeFouw et al, 2021). While the GEAR UP programs are encouraged to last for 6 to 7 years, studies have reported short-term effects of GEAR UP.…”
Section: The Present Studymentioning
confidence: 99%